2021
DOI: 10.1021/acs.jproteome.0c00847
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Investigation of the Antibacterial Mechanism of trans-Cinnamaldehyde against Escherichia coli

Abstract: Trans-Cinnamaldehyde (TC) is a widely used food additive, known for its sterilization, disinfection, and antiseptic properties. However, its antibacterial mechanism is not completely understood. In this study, quantitative proteomics was performed to investigate differentially expressed proteins (DEPs) in Escherichia coli in response to TC treatment. Bioinformatics analysis suggested aldehyde toxicity, acid stress, oxidative stress, interference of carbohydrate metabolism, energy metabolism, and protein transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…Being an electrophilic and thiol-reactive compound, t -CIN is anticipated to induce an intracellular redox disbalance [ 34 , 35 ]. This is indeed reflected by the induction of oxidative-stress-related genes upon t -CIN exposure, as demonstrated in E. coli [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Being an electrophilic and thiol-reactive compound, t -CIN is anticipated to induce an intracellular redox disbalance [ 34 , 35 ]. This is indeed reflected by the induction of oxidative-stress-related genes upon t -CIN exposure, as demonstrated in E. coli [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Being an electrophilic and thiol-reactive compound, t -CIN is anticipated to induce an intracellular redox disbalance [ 34 , 35 ]. This is indeed reflected by the induction of oxidative-stress-related genes upon t -CIN exposure, as demonstrated in E. coli [ 35 , 36 , 37 ]. Maintenance of the bacterial intracellular redox homeostasis depends on various enzymatic antioxidant systems and reducing agents such as glutathione [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suggested that aldehydes may disturb metabolic pathways, such as the pentose phosphate pathway, inducing acid stress and ROS production in E. coli cells. 63 According to previous studies, trans -cinnamaldehyde was the only compound of the three antibacterial molecules capable of completely eliminating the biofilm of E. coli , and it was the only compound possessing an aldehyde group. 64 Thus, the antifungal and anti-biofilm activities may be attributed to the aldehyde group of OCS.…”
Section: Resultsmentioning
confidence: 99%
“…The P value of the pathway enrichment was calculated based on the right-hypergeometric test and corrected with Bonferroni’s adjustment. Herein, the P value was set as two-sided hypergeometric tests and adjusted using Bonferroni’s correction, and a P value of <0.05 was considered statistically significant ( 36 ).…”
Section: Methodsmentioning
confidence: 99%